2001
DOI: 10.1159/000046094
|View full text |Cite
|
Sign up to set email alerts
|

Does Methylene Blue Protect the Kidney Tissues from Damage Induced by Ciclosporin A Treatment?

Abstract: Ciclosporin A (CsA) is the first-choice immunosuppressant universally used in allotransplantation and autoimmune diseases. However, it has been demonstrated that this drug produces negative side effects in several organs and in particular in the lymphoid organs and in the kidney. It has been suggested that the CsA causes deleterious effects because it increases the oxygen free radical production. Here we wanted to test whether antioxidants protect the kidney parenchyma from the toxicity induced by CsA. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…The results obtained in the present study are similar to those reported by some researchers [28][29][30] but differ from those reported by Rezzani et al 31 and Aksu et al 32 . The differences may be due to the difference in organ systems used, the dose and mode of application of the MB used in these studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results obtained in the present study are similar to those reported by some researchers [28][29][30] but differ from those reported by Rezzani et al 31 and Aksu et al 32 . The differences may be due to the difference in organ systems used, the dose and mode of application of the MB used in these studies.…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, systemic administration of MB has been shown to reduce oxidative stress in kidney of ciclosporine treated rats 31 . Aksu et al 32 reported that administration of MB (2 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 95%
“…As a century-old drug, MB has been in medical use for many years in various pathological conditions (41,42). The therapeutic potential of MB has been demonstrated clinically against many diseases, including endotoxin-induced lung injury, bacterial lipopolysaccharide-induced fever (43)(44)(45), cyclosporin-induced kidney injury (46), doxorubicin-induced heart injury (47), and pancreas injury induced by streptozotocin (48). Recently, MB was reported to attenuate Tau aggregation, and it is currently in phase II clinical trials for treatment of Alzheimer disease.…”
Section: Discussionmentioning
confidence: 99%
“…MB has been shown to protect against cyclosporine injury to the kidney [142] and streptozotocin injury to the pancreas [143]. MB also protects from ischemic-reperfusion injury [144], radiation [145], and enhances β-oxidation of long chain fatty acids [146].…”
Section: Clinical Uses Of Methylene Bluementioning
confidence: 99%